Cross-sector partnerships for social innovation: Drivers and barriers - Carvalho, Matilde Ferreira do Amaral Cansado (2022)
Social innovation is gaining more and more interest on different fronts. As an innovative way to deal with social problems, social innovation is an answer to several issues existing in our society. As such, not only does the third sector hand in hand with these topics but also other sectors are becoming interested, especially due to a growing global concern with social and sustainability issues that makes everyone want to be part of the solution to these problems, pressuring the public and private sectors to care about it too. From this mutual interest, cross-sector partnerships emerge, bringing together the three sectors (public, private, and third sector) with the common goal of working for social innovation. This dissertation seeks to deepen these topics through the following research question: What are the drivers and barriers to using cross-sector partnerships in social innovation, from a third sector perspective? The methodology used to reach the answer was a qualitative method of multiple case studies analysis of six cases of social innovation projects. The drivers and barriers ended up being divided into two categories: at the beginning of the partnership and in maintaining the partnership. The results intend to be useful especially to the third sector institutions and projects, giving them some insights into what drivers and barriers they may face when moving towards partnerships with other sectors, but also can be useful to the other sectors to face the perspectives of the third sector in these relationships.